Impact of wheat production technology packages adoption on smallholder farmers’ food security and income in Horo Guduru Wollega Zone, Ethiopia - Zenbaba, Oliyad Sori; Ketema, Mengistu; Jaleta, Moti; Jemal, Kedir (Springer, 2025)
Adoption of agricultural technology packages got considerable attention in enhancing smallholders’ food security and farm income in Ethiopia. However, the impact evaluation of such technology packages’ contributions to households’ food security and income are limited. This study is aimed at identifying factors affecting households’ decisions in adopting wheat technology packages and its ex-post adoption impact on their food security and wheat production income. The food consumption score and households’ dietary diversity score were used as proxy measures of households’ food security. The study employed a multinomial endogenous switching regression model to account for selection bias. Analysis results show that household decisions to adopt combinations of wheat technology packages influenced by age, sex, education level of household head, distance from markets, plots and services, phone ownership, access to credit services, agricultural cooperative membership, farm size, livestock, and farm training services. Moreover, the study shows that adoption of full wheat technology packages has a greater positive impact on households’ food security and wheat production income than adopting these packages in a few combinations or in isolation. The findings of the study suggest strengthening the provision of improved agricultural services to support farmers in adopting packages of technologies for a better food security and livelihood outcomes.